First trial and physicochemical studies on the loading of basic fuchsin, crystal violet and Black Eriochrome T on HKUST-. (22nd March 2017) - Loera-Serna, S.; Ortiz, Elba; Beltrán, Hiram I.
Abstract : We study the possibility of loading and retaining neutral (basic fuchsin), anionic (Black Eriochrome T) and cationic (crystal violet) molecules on HKUST-1. Abstract : The highly porous metal–organic framework based on copper-benzenetricarboxylate (HKUST-1, Cu3 (BTC)2, MOF-199) is used for a loading study of basic fuchsin (BF, neutral charge, ϕ = 12.40 Å molecular diameter, 50 ppm solution), crystal violet (CV, cationic charge, ϕ = 15.10 Å, 50 ppm solution) and Eriochrome Black T (EBT, anionic charge, ϕ = 15.50 Å, 80 ppm solution), as chosen molecular probes for physicochemical analysis and interactions. Characterization is carried out using XRD, FTIR, SEM, and TGA, and UV-Vis is used to determine the differential concentration of loaded dye in the MOF. The adsorption process is evaluated by three incorporation methodologies: post-synthesis (PS) and one-pot in organic (OPO) or metallic (OPM) solution. XRD cell parameters reveal the general compactness of the net through ionic (CV and EBT), dipolar (BF, CV and EBT) and van der Waals (BF, CV and EBT) dye–MOF interactions. Enhanced compactness is observed for CV due to its cationic nature and medium size; the effect is not as strong in EBT, which is anionic in nature but bigger in size, and the least compactness is observed for BF, which lacks ionic interaction with the net. The samples have crystal sizes between 34 and 57 nm, which indicate the generation of nanomaterials. The employed procedures yield crystallite size in the following order: PS < OPO < OPM. The (%) adsorption of all the dyes is above 86.93%, which is observed for the EBT-PS sample as the lowest and 99.42% for BF-PS as the highest, which evidences the high displacement of equilibrium in the studied systems to the Cu3 (BTC)2 ·dye occluded state. Thus, MOFs can be suggested as potential adsorbents/loaders of BF/CV/EBT dyes for composite material generation as well as MOF·molecule interaction studies because of their high loading ability and obtained stability as well as facile synthesis.